SIRT1 silencing confers neuroprotection through IGF‐1 pathway activation1. Issue 8 (18th April 2013) - Sansone, Luigi; Reali, Valentina; Pellegrini, Laura; Villanova, Lidia; Aventaggiato, Michele; Marfe, Gabriella; Rosa, Roberta; Nebbioso, Marcella; Tafani, Marco; Fini, Massimo; Russo, Matteo A.; Pucci, Bruna
Abstract: The following study demonstrated that, in in vitro differentiated neurons, SIRT1 silencing induced an increase of IGF‐1 protein expression and secretion and of IGF‐1R protein levels which, in turn, prolonged neuronal cell survival in presence of an apoptotic insult. On the contrary, SIRT1 overexpression increased cell death. In particular, IGF‐1 and IGF‐1R expression levels were negatively regulated by SIRT1. In SIRT1 silenced cells, the increase in IGF‐1 and IGF‐1R expression was associated to an increase in AKT and ERK1/2 phosphorylation. Moreover, neuronal differentiation was reduced in SIRT1 overexpressing cells and increased in SIRT1 silenced cells. We conclude that SIRT1 silenced neurons appear more committed to differentiation and more resistant to cell death through the activation of IGF‐1 survival pathway. J. Cell. Physiol. 228: 1754–1761, 2013. © 2013 Wiley Periodicals, Inc.